My life : Earvin "Magic" Johnson - Johnson, Earvin, 1959-; Novak, William (New York : Random House, 1992)
The story of Magic Johnson's life: his boyhood, his high school and college careers, his meteoric rise to basketball fame as a Laker, his glamorous life on the road, his hopes, fears, fulfilments and regrets.
Keywords: Johnson, Earvin, -- 1959-; Basketball players -- United States -- Biography